Answer:
i need to know what for
Step-by-step explanation:
Translation of the graph:
y = ( x + 3 )² - 2 to y = ( x - 2 )² + 2
The equations are in the form: y = a ( x - h )² + k
- 2 → 2 ( up 4 )
- 3 → 2 ( 5 to the right )
Answer:
The translation is
A ) up 4 and 5 to the right
substitution
y = 7x-26 (1)
y = 4x-11 (2)
1⇒2
7x-26=4x-11
3x=15
x=5
y = 7(5)-26
y = 9
point (5,9)
Answer:
7y-2x=-7
Step-by-step explanation:
first solve the equation in terms of y. and get the coefficient of x has your gradient slope, and use the equation of a straight line, M1=M2.
Answer:
use g o og le
Step-by-step explanation:
first, look then there are no options then use brain